Insights into Perimenopause: A Survey of Perceptions, Opinions on Treatment, and Potential Approaches - Andrea K. Wegrzynowicz; Amanda C. Walls; Myra Godfrey; Amy Beckley (Women)
Perimenopause, the transitional phase leading up to menopause, affects millions of women worldwide, yet it remains poorly understood and under-addressed in healthcare. Despite the availability of treatment options like hormone replacement therapy (HRT) and non-hormonal alternatives, the awareness and utilization of these options vary significantly among women. Here, we conducted a cross-sectional survey with 1000 adults, both men and women, from the United States and Canada. We evaluated the perceived familiarity of participants with the timing, duration, and symptoms of perimenopause, as well as their satisfaction with their treatment options and communication with their healthcare providers. We found that, in general, women and older people were more likely to feel familiar with perimenopause, although the youngest age group surveyed also reported relatively high familiarity. We also found that there is a disconnect between people reporting high familiarity with perimenopause and its symptoms but overall middling and lower familiarity with the age and duration of onset and satisfaction with treatment options. Our results suggest further investigation into where people obtain their information concerning perimenopause, as well as into how knowledge of perimenopause may vary based on demographics.